Pengaruh Dana Pihak Ketiga Dan Kredit Bermasalah Terhadap Profitabilitas Pada Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Naurah Islami Pasha; Alwi Alwi; Juwani Juwani (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of third party funds (DPK) and non-performing loans (NPL) on bank profitability proxied through Return on Assets (ROA) in the banking sub-sector listed on the Indonesia Stock Exchange (IDX), especially in the Bank Group Based on Core Capital (KBMI) IV which includes Bank Mandiri, BRI, BCA, and BNI during the 2019-2023 period. The method used is a quantitative approach with multiple linear regression testing and classical assumption testing. The results showed that partially, DPK has a positive and significant effect on ROA, while NPL has a negative and significant effect on ROA. Simultaneously, both variables also have a significant effect on ROA. The findings indicate that the effectiveness of fund raising and credit risk management are key factors in improving bank financial performance in the Indonesian banking sector.